Abstract State Machines, Alloy, B, TLA, VDM, and Z 5th International Conference, ABZ 2016, Linz, Austria, May 23-27, 2016, Proceedings - Butler, Michael; Schewe, Klaus-Dieter; Mashkoor, Atif; Biro, Miklos (Theoretical Computer Science and General Issues, 2016)
This book constitutes the refereed proceedings of the 5th International Conference on Abstract State Machines, Alloy, B, TLA, VDM, and Z, ABZ 2016, held in Linz, Austria, in May 2016. The 17 full and 15 short papers presented in this volume were carefully reviewed and selected from 61 submissions. They record the latest research developments in state-based formal methods Abstract State Machines, Alloy, B, Circus, Event-B, TLS+, VDM and Z.